Caregiver preference for reinforcement‐based interventions for problem behavior maintained by positive reinforcement. Issue 2 (21st January 2016) - Gabor, Anne M.; Fritz, Jennifer N.; Roath, Christopher T.; Rothe, Brittany R.; Gourley, Denise A.
Abstract : Social validity of behavioral interventions typically is assessed with indirect methods or by determining preferences of the individuals who receive treatment, and direct observation of caregiver preference rarely is described. In this study, preferences of 5 caregivers were determined via a concurrent‐chains procedure. Caregivers were neurotypical, and children had been diagnosed with developmental disabilities and engaged in problem behavior maintained by positive reinforcement. Caregivers were taught to implement noncontingent reinforcement (NCR), differential reinforcement of alternative behavior (DRA), and differential reinforcement of other behavior (DRO), and the caregivers selected interventions to implement during sessions with the child after they had demonstrated proficiency in implementing the interventions. Three caregivers preferred DRA, 1 caregiver preferred differential reinforcement procedures, and 1 caregiver did not exhibit a preference. Direct observation of implementation in concurrent‐chains procedures may allow the identification of interventions that are implemented with sufficient integrity and preferred by caregivers.